Large Scale Network-Centric Distributed Systems - Sarbazi-Azad, Hamid; Zomaya, Albert Y. (Hoboken, New Jersey : Wiley, 2014)
A highly accessible reference offering a broad range of topics and insights on large scale network-centric distributed systems Evolving from the fields of high-performance computing and networking, large scale network-centric distributed systems continues to grow as one of the most important topics in computing and communication and many interdisciplinary areas. Dealing with both wired and wireless networks, this book focuses on the design and performance issues of such systems. Large Scale Network-Centric Distributed Systems provides in-depth coverage ranging from ground-level hardware issues (such as buffer organization, router delay, and flow control) to the high-level issues immediately concerning application or system users (including parallel programming, middleware, and OS support for such computing systems). Arranged in five parts, it explains and analyzes complex topics to an unprecedented degree.
3.5 The Proposed Multithreaded B & B3.6 Experiments and Results; 3.6.1 Flow-Shop Instances; 3.6.2 Hardware and Software Testbed; 3.6.3 Experimental Protocol; 3.6.4 Performance Analysis; 3.6.5 Page Faults; 3.6.6 Context Switches; 3.7 Conclusion; References; Part 2: Pervasive/Ubiquitous Computing and Peer-to-Peer Systems; 4 Large-Scale P2P-Inspired Problem-Solving: A Formal and Experimental Study; 4.1 Introduction; 4.1.1 Motivations; 4.1.2 Contribution and Results; 4.1.3 Related Works; 4.1.4 Outline; 4.2 Background; 4.3 A Pure Peer-to-Peer B & B Approach; 4.3.1 Preliminaries.
4.3.2 Information Sharing and Work Distribution.
Includes bibliographical references and index.
Print version record.
Keywords: Computer science; Electronic data processing -- Distributed processing; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Computer science; Electronic data processing -- Distributed processing; Electronic books